Assessment of Lumbar Lordosis and Lumbar Core Strength in Information Technology Professionals - Roma Satish Mehta; Sanket Nagrale; Rachana Dabadghav; Savita Rairikar; Ashok Shayam; Parag Sancheti (Asian Spine Journal, 2016)
Study DesignObservational study.PurposeTo correlate lumbar lordosis and lumbar core strength in information technology (IT) professionals.Overview of LiteratureIT professionals have to work for long hours in a sitting position, which can affect lumbar lordosis and lumbar core strength.MethodsFlexicurve was used to assess the lumbar lordosis, and pressure biofeedback was used to assess the lumbar core strength in the IT professionals. All subjects, both male and female, with and without complaint of low back pain and working for two or more years were included, and subjects with a history of spinal surgery or spinal deformity were excluded from the study. Analysis was done using Pearson's correlation.ResultsFor the IT workers, no correlation was seen between lumbar lordosis and lumbar core strength (r=–0.04); however, a weak negative correlation was seen in IT people who complained of pain (r=–0.12), while there was no correlation of lumbar lordosis and lumbar core in IT people who had no complains of pain (r=0.007).ConclusionsThe study shows that there is no correlation of lumbar lordosis and lumbar core strength in IT professionals, but a weak negative correlation was seen in IT people who complained of pain.